Characterization of native isolates of Beauveria bassiana and its pathogenicity to Hypothenemus hampei, en Tabasco, Mexico. (2016)
In order to obtain native isolates of Beauveria bassiana with potential to control Hypothenemus hampei, 12 strains were isolated and characterized according to physiological and pathogenicity variables. Mycelia growth (MG), germination rate and conidial production (CP) in Sabouraud dextrose agar media + 0.1% of yeast extract (SDA+YE), were assessed at 25, 30 and 35 °C. In addition, the conidial production on rice was evaluated at 25 °C. There were differences (P < 0.001) in the MG of the isolates. The favorable temperature for MG ranged between 25 and 30 °C. The time required to 50% of conidial germination (TG50) ranged from 12.6 to 15.9 h, and the TG90 ranged from 16.9 to 61.5 h. The best TG50 and TG90 were obtained at 25 and 30 °C. The optimum temperature for germination, of the majority of the isolates, was 30 °C. There were differences (P < 0.001) on the PdC in the SDA+YE media, and the optimum temperature for the production of conidia was 25 °C. Thus, there were differences (P < 0.001) in the production of conidia in rice. The pathogenic effectiveness of the isolates of B. bassiana on H. hampei was 100%, to the 144 h. Letal time to kill 50% of the population (TL50) ranged from 71.8 to 104 h; as well as, the TL90 ranged from 91.8 to 132.8 h. Native strains BbTcf9, BbTcf5 and BbTcf1 were selected for its evaluation under field conditions.